Antiepileptic drugs: newer targets and new drugs - Chawan, Vihang S.; Phatak, Abhishek M.; Gawand, Kalpesh V.; Badwane, Sagar V.; Panchal, Sagar S. (International Journal of Basic & Clinical Pharmacology, 2016)
Epilepsy is a common neurological disorder affecting 0.5-1% of the population in India. Majority of patients respond to currently available antiepileptic drugs (AEDs), but a small percentage of patients have shown poor and inadequate response to AEDs in addition to various side effects and drug interactions while on therapy. Thus there is a need to develop more effective AEDs in drug resistant epilepsy which have a better safety profile with minimal adverse effects. The United States food and drug administration (USFDA) has approved eslicarbazepine acetate, ezogabine, perampanel and brivaracetam which have shown a promising future as better AEDs and drugs like ganaxolone, intranasal diazepam, ICA- 105665, valnoctamide, VX-765, naluzotan are in the pipeline.